THE GABBRO AND SERPENTINIZED PERIDOTITE OF BONASSOLA (BRACCO-LEVANTO OPHIOLITE, ITALY) - AN EXTREMELY LOW NATURAL RADIATION AREA TO IMPROVE IN SITU GAMMA SPECTROMETRY - Braga, Roberto; Cinelli, Giorgia (Ofioliti, 2014)
Outcrops of dunite, serpentinized peridotite and clinopyroxene-rich coarse gabbro around Bonassola (Bracco-Levanto ophiolite, NW Italy) have been analyzed for natural radionuclides using γ-spectrometry. The very low activity concentrations of natural radionuclides in the dunite outcrop (< 9.0 Bq kg-1 226Ra; < 3.5 Bq kg-1 228Ac and < 25 Bq kg-1 40K) indicate that this site is characterised by a very low natural radiation for both cosmic (being at sea level) and terrestrial contributions. Before starting a field radiometric survey it is important to assess the local background, i.e. the g radiation that does not originate from rock, in order to correct the measurements for the local background. Contrary to the general practice regarding the background radiation in γ-spectrometry measurements, the investigated mafic-ultramafic outcrops has been used to estimate the detection limits for in situ measurement of 238U, 232Th and 40K using sodium iodine (NaI) scintillator detectors. These results have proved useful to quantify the minimum detectable amount of activity (MDA) of 238U, 232Th and 40K for the NaI detector; the MDA points at sub ppm levels for 238U and 232Th and 0.01 wt% K2O. This study also permits to assess the radiological risk of dimension stones that are petrographically similar to the serpentinized ultramafics occurring in the Bracco-Levanto ofiolite. The comparison of the activity concentration index I, defined by the EU Basic Safety Standards Directive and depending on the activity concentrations of 226Ra, 232Th and 40K, with other stones used as building material, indicates that the Bonassola mafic-ultramafic rocks provide a negligible contribution to the indoor gamma radiation dose.